RELASI ANTARA LAFAZ-LAFAZ DALAM USHUL FIQH DENGAN PROBLEMATIKA HUKUM KELUARGA - Nurul Mahmudah; Nency Dela Octora (Institut Agama Islam Negeri Metro, 2022)
This paper discusses the understanding of pronunciation in ushul. The fiqh that needs to be known is due to the existence of clear and unclear pronunciation and how it relates when analyzing family law problems/ problems such as the problem of registering marriages. This paper makes use of descriptive qualitative research methods. Literature study becomes a reference for material reviewers and is analyzed in depth. As for the results of this paper, Judging from the kezahiran a lafaz, the recording of a marriage contract is legally obligatory as is required in a mu`amalah contract. Written evidence can be used for matters relating to the continuation of the marriage contract. With this evidence, the couple can avoid harm in the future because this written evidence can legally process various household issues, especially as the most valid evidence in religious courts.